2020
DOI: 10.7150/jca.48495
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Polyunsaturated Fatty Acids with Tumor Progression in a Lean Non-Alcoholic Steatohepatitis-Associated Hepatocellular Carcinoma Mouse Model

Abstract: Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in Western countries. While obesity and diabetes are the hallmarks of NAFLD, it also develops in lean individuals in the absence of metabolic syndrome, with a prevalence of 7 percent in the U.S. and 25-30 percent in some Asian countries. NAFLD represents the spectrum of liver disease, starting with excess liver fat accumulation (NAFL) that can progress to nonalcoholic steatohepatitis (NASH), cirrhosis and ultimately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…For instance, an increase in FFA 16:1 [90] and a decrease in the FA composition (18:2 n-6, 20:4 n-6, 16:0 and 18:1 n-9) in the plasma phospholipids of HCC patients have been reported [91]. In turn, in a NASH-associated HCC mouse model, reduced levels of FFAs 18:3 n-3, 20:5 n-3, 22:6 n-3, and 18:2 n-6 were found [92]. An untargeted lipidomic analysis revealed that the blood levels of almost all lipid groups were decreased in HCC patients when compared to CLD subjects and that many specific lipid classes were upor dowregulated in HCC patients with respect to healthy controls [45].…”
Section: Hepatocellular Carcinoma and Lipid Alterationsmentioning
confidence: 96%
“…For instance, an increase in FFA 16:1 [90] and a decrease in the FA composition (18:2 n-6, 20:4 n-6, 16:0 and 18:1 n-9) in the plasma phospholipids of HCC patients have been reported [91]. In turn, in a NASH-associated HCC mouse model, reduced levels of FFAs 18:3 n-3, 20:5 n-3, 22:6 n-3, and 18:2 n-6 were found [92]. An untargeted lipidomic analysis revealed that the blood levels of almost all lipid groups were decreased in HCC patients when compared to CLD subjects and that many specific lipid classes were upor dowregulated in HCC patients with respect to healthy controls [45].…”
Section: Hepatocellular Carcinoma and Lipid Alterationsmentioning
confidence: 96%
“…90 Conversely, serum levels of PUFAs are decreased in the blood of patients with HCC. 90 , 118 , 122 …”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“…Several studies have demonstrated that a high-fat, high-cholesterol diet can trigger HCC in mice, 122 , 134 , 140 , 141 via a neoplastic transformation of hepatocytes caused by broad transcriptional deregulation of genes involved in metabolic pathways (`metabolism in cancer´ hallmark) and calcium signalling. 140 It has been shown that statins, which block hepatic cholesterol synthesis, protect against HCC 142 and CCA 143 development, as well as resulting in decreased risk of mortality.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“…The Institutional Animal Care and Use Committee at the University of Nebraska Medical Center approved this study (Protocol #: 17–018) and it was also conducted in compliance with the ARRIVE guidelines. Male (n = 103) and female (n = 25) C57BL/6N mice (Charles River Laboratories) were allowed to acclimate and housed as previously described starting at 3 weeks of age [ 15 ]. They were housed in a temperature-, humidity-, and ventilation-controlled vivarium on a 12-h light/dark cycle in specific pathogen-free conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a genetic murine model of NASH revealed distinct patterns of serum and tissue fatty acid levels that correlate with early-stage HCC [ 13 ]. Higher levels of free fatty acids were observed in the livers of mice with diet-induced NAFLD [ 14 ] and polyunsaturated fatty acids were reduced in the plasma of mice with lean NASH-HCC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%